Migration is a natural process to distribute labor surplus in origin regions to destination regions having a high level of labor demand, but in recent years migration causes labor surplus and unemployment in the destination region. The objective of this paper is to analyze the influence of migration on labor market behavior and to evaluate the impact of internal migration policy on labor market behavior in Indonesia. To reach this objective, a simultaneous equation model containing 15 structur - Safrida .; Bonar M. Sinaga; Hermanto Siregar; Harianto . (Forum Pasca Sarjana, 2008)
Migration is a natural process to distribute labor surplus in origin regions to destination regions having a high level of labor demand, but in recent years migration causes labor surplus and unemployment in the destination region. The objective of this paper is to analyze the influence of migration on labor market behavior and to evaluate the impact of internal migration policy on labor market behavior in Indonesia. To reach this objective, a simultaneous equation model containing 15 structural equations and 5 identities equations are constructed. The analysis use time series 1985-2006 data. Model was estimated by 2SLS method and simulation was used the Newton method. The results of this research indicated that migration influence labor supply in Jawa, Kalimantan and other island. Factors that influence labor demand in Java are amount of industry and government development expenditure, but in Sumatera, Kalimantan, Sulawesi, and other island influenced by total investment, government development expenditure and lag labor demand. The impact of internal migration policy on labor market by way of increasing minimum wage can not solve labor market problem because the policy cause increase unemployment in each island. The impact of increasing minimum wage and government development expenditure can solve labor market problem through decreasing unemployment, although average wage in each island is increasing. The policy can also solve distribution of population by way of decreasing migration to Jawa. Key words: internal migration, labor market